Combating Microbial Infections Using Metal-Based Nanoparticles as Potential Therapeutic Alternatives - Rajwinder Kaur; Kirandeep Kaur; Mohammad H. Alyami; Damanpreet Kaur Lang; Balraj Saini; Mohammad F. Bayan; Balakumar Chandrasekaran (MDPI AG, 2023)
The nature of microorganisms and the efficiency of antimicrobials have witnessed a huge co-dependent change in their dynamics over the last few decades. On the other side, metals and metallic compounds have gained popularity owing to their effectiveness against various microbial strains. A structured search of both research and review papers was conducted via different electronic databases, such as PubMed, Bentham, Springer, and Science Direct, among others, for the present review. Along with these, marketed products, patents, and Clinicaltrials.gov were also referred to for our review. Different microbes such as bacteria, fungi, etc., and their diverse species and strains have been reviewed and found to be sensitive to metal-carrying formulations. The products are observed to restrict growth, multiplication, and biofilm formation effectively and adequately. Silver has an apt use in this area of treatment and recovery, and other metals like copper, gold, iron, and gallium have also been observed to generate antimicrobial activity. The present review identified membrane disruption, oxidative stress, and interaction with proteins and enzymes to be the primary microbicidal processes. Elaborating the action, nanoparticles and nanosystems are shown to work in our favor in well excelled and rational ways.